Pengaruh Implementasi Kebijakan Online Single Submission, Kompetensi Pegawai Dan Pelatihan Terhadap Pelayanan di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu DKI Jakarta - Mega Fitria Sari; Saifullah (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to analyze the effect of the implementation of the OSS policy, employee competence, and training on services at the Investment and One-Stop Integrated Service Office (DPMPTSP) of DKI Jakarta. The research method used is quantitative research with a questionnaire as the data collection technique with a sample size of 154 individuals selected through probability sampling. The results show that the implementation of the OSS policy, employee competence, and training individually have a positive and significant effect on service, and collectively, the three independent variables contribute positively and significantly to services at DPMPTSP DKI Jakarta. This is supported by an F value of 64.003, which is greater than the F table value of 2.66, and a significance level of 0.000, which is smaller than the significance probability α = 0.05. The coefficient of determination is 0.561, indicating that the combined effect of the OSS policy implementation, employee competence, and training accounts for 56.1% of the variation in the service variable, while the remaining 43.9% is affected by other variables not included in this research.